Preparation of sightseeing trip text and elaboration of methodical development of such trip (on the example of the city of Chernivtsi - Korol, Oleksandr; Ivanunik, Vitalii (Journal of Education, Health and Sport, 2024)
The article examines the theoretical and methodological approaches to the preparation of sightseeing trip text and elaboration of methodical development of such trip as well as their practical application on the example of the city of Chernivtsi, Ukraine. It is established that the sightseeing trip text is divided into control and individual. The control text serves as a standard and contains the most important material necessary to reveal the theme of the trip. At the same time, the individual text of the excursion is compiled according to the route and structured on the basis of sightseeing objects, which are devoted to the main questions. The methodical development of the sightseeing trip is considered, which indicates how the route runs, which objects are visited, where there are places for stops and localization of groups, which sub-topics and main questions are revealed near certain sightseeing objects, etc. This information is presented in a systematic manner, with reference to each other in time and space.